Protecting asylum-seekers prior to determination of refugee status: reinterpreting the refugee convention and assessing contemporary state practice on non-refoulement - Hamid, Abdul Ghafur@Khin Maung Sein; Phiri, Shaban Abdul Majeed (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
The present decade is confronted with unprecedented refugee crises, dwarfing all similar refugee crises ever witnessed by mankind before. The plight of asylum-seekers, particularly prior to the determination of their refugee status by the host country, is of great concern to the UNHCR and the international community, as this is the time when they are most vulnerable. The sad situation of these asylum-seekers, their sufferings on small boats being packed like sardines on angry seas, and their pain in the hands of cruel human traffickers, beg the crucial question of whether they are protected in any way by international refugee law or left unprotected. With a view to answering this question, the present study applies the legal doctrinal method and attempts a holistic interpretation of articles 1A(2), 31(1) and 33 of the 1951 Refugee Convention. The study finds that the term ‘refugee’ in these articles is in effect referring to ‘asylum-seekers’ who fulfil the constituent elements of a refugee under the Convention and that these asylum-seekers cum refugees are protected by the Convention even before the regularisation of their refugee status. The key protection stems from the principle of non-refoulement. State practice nevertheless is not encouraging and potential States of refuge are very weak in honouring this principle, which is a corner stone of international refugee law. The study concludes with suggestions for resolving this core issue.